Research in the specialty of Obstetrics and Gynecology: An ongoing problem? - Matzumura Kasano, Juan Pedro (2019)
We welcome the readers of our magazine, we appreciate their preference, their important contributions and we ratify the commitment to continue working to share the research of the specialty, in the assurance that they will be useful in their medical practice. Currently in developed countries, research and innovation show a sustained growth, while in countries like ours, progress is insufficient. Some studies report that no Latin American university is among the 100 best universities in the world and that Latin America occupies the last places. In recent years, only five universities in the country stand out in the field of research, but in places that are not privileged; They are the National University of San Marcos, National University of Engineering, Agrarian University of La Molina, Pontificia Universidad Católica del Perú and Universidad Peruana Cayetano Heredia.